Translating norms from Europe to Turkey: Turkey in the Bologna Process - Onursal-Besgul, Ozge (Routledge Journals, Taylor & Francis Ltd, 2017)
This article focuses on the structural changes Turkish higher education is going through as a result of Turkey's integration into the European educational space. The focus of the article is the process of policy transfer. For this purpose, the article outlines the changes in Turkish higher education comprehensively to explain the dynamics of the policy transfer. Creation of a national qualifications system and establishment of a quality assurance system are given as examples of policy transfer. The article concludes that while the system is becoming more student-centred, change in higher education is happening in a very top-down fashion, where participation of relevant stakeholders is not ensured.
Keywords: Turkey; Bologna Process; Higher Education; Policy Transfer; Policy Transfer; Higher-Education; Europeanisation; Governance